(untitled) (KIUT Publication, 2025)
Periodontitis is not merely an oral disease; it is a chronic inflammatory process affecting the entire body, including brain health. Chronic inflammation leads to the excessive production of inflammatory mediators (cytokines, interleukins, TNF-alpha, and others). These mediators can circulate in the blood to the brain, triggering inflammation in the central nervous system. Periodontitis is the chronic inflammation of the tissues surrounding the teeth, primarily caused by bacteria. This disease damages the bone and tissues supporting the teeth. Dementia is the decline of cognitive abilities (memory, thinking, decision-making), often age-related, with conditions such as Alzheimer’s disease contributing to its development.